METAPHOR IN GURO-GURO ARON SONGS - Sembiring, Jeri Claudius; DIRGEYASA, I WY (Universitas Negeri Medan, 2020)
The objectives of this study were to find out meanings, what, how, and why the author conveys Metaphor in Guro-guro Aron Songs . This study was conducted using descriptive qualitative research. The data of this study were taken from Guro “ guro Aron song lyrics by Salamah Br. Barus. The sources of the data were ;˜Simulih Karaben™,perbual™,bencah buruk™.Kelengi aku™,and Sayang kel aku. The data were analyzed by using Harford™s theory. 1) The writer found there were three types of metaphor namely, conceptual metaphor (44,4%), ontological metaphor (36,3%) and orientational metaphor (18,1%). 2) the meaning of metaphor in the Guro “ guro Aron Songs. 3) There were reason the guro-guro aron why the author conveys metaphor through the lyrics of guro-guro aron album based on life and love, it interpreted by tribal leader who knows all the meaning where each lines has a deep meaning.